This Distracted Globe : Worldmaking in Early Modern Literature - Newman, Karen, 1949-; Goldberg, Jonathan; Frank, Marcie (Book collections on Project MUSE., 2016)
These essays investigate the materiality of the world in Spenser, Cary and Marlowe; its sociability, sexuality and sovereignty in Shakespeare; and the universality of spirit, gender and empire in Vaughan, Donne and the dastan (tale) of Chouboli, a Rastanjani princess.